Parallel Justice and Fundamental Rights: A Critical Analysis of Jirga and Panchayat Systems in Pakistan - Dr. Sajid Sultan; Muhammad Ahsan Iqbal Hashmi; Syed Mohammad Tahir Gohar (Social Science Review Archives, 2025)
The continued existence of informal adjudicatory institutions like Jirgas and Panchayats in Pakistan depicts a most compound nexus between the inculcated cultural mores and the theoretically servient constitutional ordeal. They are customary based and grounded in community agreement and they continue to mediate in conflicts and maintain social order, particularly in the rural and tribal hinterland of the country where formal state structures are still immature or viewed as remote. As advocates affirm that such forums are indigenous systems through which community harmony may be promoted and a cost-effective method of resolving disputes is developed, they also create a basis of serious human-rights issues. The rules used by these organs systematically violate clauses under the Constitution of Pakistan that guarantee equality, due process and entitlement to fair trial in Article 10(A) of the Constitution of Pakistan. Further, the results of such fora - specifically the ones that of women and marginalised communities have often been outcome of violation to the international human rights of Pakistan in the light of the international instruments like the International Covenant on Civil and Political Rights (ICCPR) and the Convention on the Elimination of All Forms of Discrimination against women (CEDAW). The paper is a critical inquiry into the constitutional and human-rights consequences of Jirga and Panchayat systems on the basis that even though the systems are embedded in the social structure, they are extralegal systems that operate against the very fabric of the state which constitutes the pillars of fundamental rights. It concludes that community-based justice, though perhaps one of a relative supplement, needs to be turned into law and rights-independent check-balances to halt the continuation of existing systemic injustices in the guise of tradition.